Evidence for the Involvement of the Master Transcription Factor NF-κB in Cancer Initiation and Progression - Puar, Yu Rou (Biomedicines, 2018)
Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) is responsible for the regulation of a large number of genes that are involved in important physiological processes, including survival, inflammation, and immune responses. At the same time, this transcription factor can control the expression of a plethora of genes that promote tumor cell proliferation, survival, metastasis, inflammation, invasion, and angiogenesis. The aberrant activation of this transcription factor has been observed in several types of cancer and is known to contribute to aggressive tumor growth and resistance to therapeutic treatment. Although NF-κB has been identified to be a major contributor to cancer initiation and development, there is evidence revealing its role in tumor suppression. This review briefly highlights the major mechanisms of NF-κB activation, the role of NF-κB in tumor promotion and suppression, as well as a few important pharmacological strategies that have been developed to modulate NF-κB function.